Expanded phenotypic spectrum of JAG1‐associated diseases: Central conducting lymphatic anomaly with a pathogenic variant in JAG1. Issue 5 (12th January 2021) - Li, Dong; Sheppard, Sarah E.; Peroutka, Christina; Barnes, Caitlin; Reid, Janet R.; Smith, Christopher L.; Dori, Yoav; Hakonarson, Hakon
Abstract :